Positron-emission tomography–based staging reduces the prognostic impact of early disease progression in patients with follicular lymphoma. (February 2020) - Batlevi, Connie L.; Sha, Fushen; Alperovich, Anna; Ni, Ai; Smith, Katy; Ying, Zhitao; Gerecitano, John F.; Hamlin, Paul A.; Horwitz, Steve M.; Joffe, Erel; Kumar, Anita; Matasar, Matthew J.; et al.
Abstract: Background: Previous studies reported that early progression of disease (POD) after initial therapy predicted poor overall survival (OS) in patients with follicular lymphoma (FL). Here, we investigated whether pre-treatment imaging modality had an impact on prognostic significance of POD. Methods: In this retrospective study, we identified 1088 patients with grade I–IIIA FL; of whom, 238 patients with stage II–IV disease were initially treated with rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP), and 346 patients were treated with rituximab-based chemotherapy. Patients (N = 484) from the FOLL05 study served as an independent validation cohort. We risk-stratified patients based on pre-treatment radiographic imaging (positron-emission tomography [PET] versus computed tomography [CT]) and early POD status using event-defining and landmark analyses. A competing risk analysis evaluated the association between early POD and histologic transformation. Results: In the discovery cohort, patients with POD within 24 months (PFS24) of initiating R-CHOP therapy had a 5-year OS of 57.6% for CT-staged patients compared with 70.6% for PET-staged patients. In the validation cohort, the 5-year OS for patients with early POD was 53.9% and 100% in CT- and PET-staged patients, respectively. The risk of histologic transformation in patients whose disease progressed within one year of initiating therapy was higher in CT-staged patients than in PET-staged patients (16.7% versus 6.3%, respectively), which was associated with a 9.7-fold higher risk of death. Conclusion: In FL, pre-treatment PET staging reduced the prognostic impact of early POD compared with CT staging. Patients with early POD and no histologic transformation have an extended OS with standard therapy. Highlights: Early progression after first-line treatment in follicular lymphoma is a marker of poor prognosis. Positron-emission tomography (PET) staging possibly identifies patients with highest risk of poor outcomes. PET staging reduces the prognostic impact of early progression likely by excluding patients with early transformation. Patients with early progression and early transformation have the highest risk of poor outcomes.